Antioxidant, anti-cholinesterase, anti-α-glucosidase and prebiotic properties of beta-glucan extracted from Algerian barley - Saad Mebrek; Hanene Djeghim; Yamina Mehdi; Asma Meghezzi; Sirajudheen Anwar; Nasser A Ali Awadh; Mohammed Benali (International Journal of Phytomedicine, 2018)
Beta-glucan, such as barley-derived beta-glucan (BBG), are homopolysaccharides that have attracted attention by their nutritional and therapeutic properties. The aim of this study was to evaluate the antioxidant power of BBG extracted from local Algerian variety of barley (SAIDA 183), and its acetylcholinesterase, alpha glucosidase inhibitory activity as well as its prebiotic potential by fermentation with lactic acid bacteria isolated from camel’s milk, namely lactococcuslactisssplactis (Lc.l.l) and leuconostocmesenteroidesspmesenteroides (Ln.m.m). The results revealed that BBG exhibited low activity against DPPH and ferric-reducing power (IC50 4018.61 ± 656.69 and A0.5 at 359.88 ±63.64 µg/mL respectively), in contrast to other antioxidant tests (ABTS, Beta-carotene and CUPRAC) where BBG demonstrated a moderate activity (IC50 529.91 ±26.37, IC50 161.013±13.322, A0.5 529.79 ± 48.65 µg/mL). The scavenging ability of hydroxyl radical and superoxide radical by BBG with an IC50 at 2268.38±101.57 µg/mL and IC50 345.26± 62.32 µg/mL, respectively, while enzymatic inhibition by BBG exhibited for AChE at IC50 859.164 ±64.46 μg/mL , BChE at IC50 at 725.470 ±30.95 , α-Amylase inhibitory activity at IC50 2986.785 ± 37.046 . The bacterial growth of the two strains used in this study is favorably affected by the use of BBG as the only carbon source, in comparison with glucose as a control. In light of these findings, it can be concluded that BBG have shown moderate antioxidant and enzyme inhibitory activities and can be used as a prebiotic by acting synergistically with probiotics in functional food matrices.